Faktor Dominan yang Berhubungan dengan Self Care pada Diabetisi - Muhammad Irfan Nugraha; Siti Badriah; Fitrian Rayasari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Diabetes Mellitus self care is a daily action that must be done by people with diabetes independently. Self care activities are carried out to control blood glucose. The factors that influence diabetes mellitus self care are age, gender, education, duration of diabetes, knowledge, self efficacy, family support, motivation and health care provider communication. The study aims to identify the dominant factors associated to self care in people with diabetes in the Working Area of the Tirawuta Public Health Center. The research method used was analytical survey design with cross sectional approach. The sampling technique used purposive sampling technique, with sample size of 88 respondents. Data were analyzed using Chi-square test and logistic regression test. The result showed that there was relationship between knowledge, self efficacy, family support, motivation and providing information and education with self care (p